A Study on Differential Type Monostable Multivibrator Using CMOS-XOR/XNOR Gate - Hirotoshi Sasaki; Amphawan Julsereewong; Hiroshi Isoguchi; Mitsutoshi Yahara; Kuniaki Fujimoto; Hirofumi Sasaki (My University, 2011)
In the differential type monostabel multivibirator using CMOS-XOR/XNOR gates, there is a circuit configuration that the operation of two elements becomes the same in stable sate and the metastable state. And, these circuits has the up mode and down mode operations. Furthermore, the metastable state is not influenced trigger repetition rate, and it is shown by a simple formula expression.
Keywords: XNOR gate; Multivibrator; Metastability; Spice; XOR gate; Advanced Sensor and Control Systems